+0  
 
0
454
1
avatar+137 

if someone could help me with this (and maybe another like it) it would be greatly appreciated

ive been stuck on this topc for a while now.

 May 12, 2017
 #1
avatar+98196 
+3

a) ( f - g)  (x)   

 

Just  subtract  g from f.......and we have

 

  f     -        g            =

 

3*8x  -  ( 2*8x + 2)  =

 

1 * 8x - 2  =

 

8x  - 2

 

 

b)    (f - g) (2)........using what we already have, we just want to substitute  "2"  for "x"  in the above result.....so 

 

82   -  2   =

 

64  -   2   =

 

62

 

 

cool cool cool

 May 12, 2017

39 Online Users

avatar
avatar
avatar
avatar